The High Resolution Stereo Camera (HRSC) of Mars Express and its approach to science analysis and mapping for Mars and its satellites. (July 2016) - Gwinner, K.; Jaumann, R.; Hauber, E.; Hoffmann, H.; Heipke, C.; Oberst, J.; Neukum, G.; Ansan, V.; Bostelmann, J.; Dumke, A.; Elgner, S.; Erkeling, G.; et al.
Abstract: The High Resolution Stereo Camera (HRSC) of ESA׳s Mars Express is designed to map and investigate the topography of Mars. The camera, in particular its Super Resolution Channel (SRC), also obtains images of Phobos and Deimos on a regular basis. As HRSC is a push broom scanning instrument with nine CCD line detectors mounted in parallel, its unique feature is the ability to obtain along-track stereo images and four colors during a single orbital pass. The sub-pixel accuracy of 3D points derived from stereo analysis allows producing DTMs with grid size of up to 50 m and height accuracy on the order of one image ground pixel and better, as well as corresponding orthoimages. Such data products have been produced systematically for approximately 40% of the surface of Mars so far, while global shape models and a near-global orthoimage mosaic could be produced for Phobos. HRSC is also unique because it bridges between laser altimetry and topography data derived from other stereo imaging instruments, and provides geodetic reference data and geological context to a variety of non-stereo datasets. This paper, in addition to an overview of the status and evolution of the experiment, provides a review of relevant methods applied for 3D reconstruction and mapping, and respective achievements. We will also review the methodology of specific approaches to science analysis based on joint analysis of DTM and orthoimage information, or benefitting from high accuracy of co-registration between multiple datasets, such as studies using multi-temporal or multi-angular observations, from the fields of geomorphology, structural geology, compositional mapping, and atmospheric science. Related exemplary results from analysis of HRSC data will be discussed. After 10 years of operation, HRSC covered about 70% of the surface by panchromatic images at 10–20 m/pixel, and about 97% at better than 100 m/pixel. As the areas with contiguous coverage by stereo data are increasingly abundant, we also present original data related to the analysis of image blocks and address methodology aspects of newly established procedures for the generation of multi-orbit DTMs and image mosaics. The current results suggest that multi-orbit DTMs with grid spacing of 50 m can be feasible for large parts of the surface, as well as brightness-adjusted image mosaics with co-registration accuracy of adjacent strips on the order of one pixel, and at the highest image resolution available. These characteristics are demonstrated by regional multi-orbit data products covering the MC-11 (East) quadrangle of Mars, representing the first prototype of a new HRSC data product level. Highlights: We present an overview of the main characteristics and operational achievements of HRSC after ten years in orbit. Demonstrate significant improvements in HRSC data product accuracy based on in-flight data. Present a new HRSC data product level based on integration of data from multiple orbits. Review methods and exemplary results for mapping and science analysis, typically based on precise co-registration and joint analysis of DTMs and orthoimages.